Analisis Manajemen Pengaduan Pelayanan Publik : Studi pada Aplikasi "Wargaku" Di Pemerintah Kota Surabaya - kartika sari, yuyun eka (Jurnal Inovasi Administrasi Negara Terapan, 2025)
Public complaints are important for the government to see how successful it is in implementing activities. Public complaints are an important element for regional agencies, because complaints aim to correct deficiencies in activities that have been implemented. The WargaKu application is an application used by the people of the city of Surabaya to submit complaints. In its implementation, several problems were still found. The first problem is that there are several reports that use other people's identities to the wrong address and there is no further response from the relevant parties regarding the reporting that has been done by the reporter on the WargaKu Surabaya application. This research aims to determine and analyze public service complaint management through the WargaKu application. The research method used is (library research), namely a method of collecting by understanding and studying theories from various literature. By using complaint management theory based on Tjiptono's theory, namely: Commitment, Visible, Accessible, Simplicity, Speed, Fairness, Confidential, Records, Resources and Remedy. What is hoped from the results of this research is that the WargaKu application will become a bridge to connect complaints and aspirations of the community with related agencies, so that the problems expressed can be conveyed and receive quick and appropriate handling.